Perusahaan Nasrieq dan Rakan-Rakan / Mohd Nasrieq Mohd Sarip Yadin ... [et al.] - Mohd Sarip Yadin, Mohd Nasrieq; Mohamed, Ahmad Nadzri; Fabil, Aliuddin Azmi; Mustapha, Amiruddin; Nordin, Mohd Bahar; Kasirun, Mohd Hafiz (Faculty of Information Management, 2006)
Perusahaan Nasrieq dan Rakan-Rakan is the name of our business venture and it is mainly serves as a restaurant which offers a variety range of burger serving style and other types of fast food. Because of the separation between our administrative office and the business premise, we have decided to call our burger booth as Burger Raya. Our partnership form of business consists of six people which contribute same amount of monetary capital.